Corporate emotional intelligence : being human in a corporate world - Chick, Gareth (Critical Publishing, 2018)
An original analysis of how human behaviour is conditioned within corporate cultures, and how managers come to adopt unconscious controlling habits that are counter-productive, inhibit growth, and create cultures of fear.